2009
DOI: 10.1080/15374410902976296
|View full text |Cite
|
Sign up to set email alerts
|

Why is Past Depression the Best Predictor of Future Depression? Stress Generation as a Mechanism of Depression Continuity in Girls

Abstract: This study examined whether a transactional interpersonal life stress model helps to explain the continuity in depression over time in girls. Youth (86 girls, 81 boys; M age = 12.41, SD = 1.19) and their caregivers participated in a three-wave longitudinal study. Depression and episodic life stress were assessed with semi-structured interviews. Path analysis provided support for a transactional interpersonal life stress model in girls but not in boys, wherein depression predicted the generation of interpersona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
97
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 80 publications
(139 reference statements)
12
97
0
Order By: Relevance
“…In turn, although W 2 dependent achievement stress and W 3 depressive symptoms were significantly positively correlated, W 2 dependent achievement stress did not predict elevations in depressive symptoms over time. This finding is consistent with one previous study in which dependent interpersonal, but not dependent noninterpersonal, life stress prospectively predicted depressive symptoms in girls (Rudolph et al 2009). The experience of dependent interpersonal stress may influence self-perceptions more robustly than dependent achievement stress, such that relationship disturbances create more negative self-appraisals than self-generated achievement stressors and, consequently, are a more robust predictor of depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…In turn, although W 2 dependent achievement stress and W 3 depressive symptoms were significantly positively correlated, W 2 dependent achievement stress did not predict elevations in depressive symptoms over time. This finding is consistent with one previous study in which dependent interpersonal, but not dependent noninterpersonal, life stress prospectively predicted depressive symptoms in girls (Rudolph et al 2009). The experience of dependent interpersonal stress may influence self-perceptions more robustly than dependent achievement stress, such that relationship disturbances create more negative self-appraisals than self-generated achievement stressors and, consequently, are a more robust predictor of depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, previous work showed that a history of depressive symptoms may have a cumulative effect on maladjustment (Wickrama & Wickrama, 2010), suggesting that the prospective associations between loneliness and depressive symptoms could be stronger for people with an enduring history of depression. Furthermore, certain depression theories propose interpersonal stress (related to loneliness) as underlying mechanisms in the continuity of depression (e.g., interpersonal stress generation; Rudolph, Flynn, Abaied, Groot, & Thompson, 2009). Likewise, certain loneliness theories suggest depressotypic characteristics as underlying mechanisms in the continuity of loneliness (e.g., lowered reward response to positive events; Cacioppo & Hawkley, 2009).…”
Section: Directions For Future Researchmentioning
confidence: 97%
“…In addition, for girls only, depression is also self-perpetuating as it contributes to interpersonal stress (Rudolph et al 2009). Compared to boys, girls report more social-evaluative concerns regarding the quality of their close relationships and the judgments they receive from others (Rose and Rudolph 2006).…”
Section: Gender-related Effects and Ethnic Differencesmentioning
confidence: 98%